2007
DOI: 10.1029/2007gl030302
|View full text |Cite
|
Sign up to set email alerts
|

Pacific meridional mode and El Niño—Southern Oscillation

Abstract: [1] We present intriguing evidence that the majority of El Niño events over the past four decades are preceded by a distinctive sea-surface warming and southwesterly wind anomaly in the vicinity of the Intertropical Convergence Zone (ITCZ) during the boreal spring. This phenomenon, known as the Meridional Mode (MM), is shown to be intrinsic to the thermodynamic coupling between the atmosphere and ocean. The MM effectively acts as a conduit through which the extratropical atmosphere influences ENSO. Modeling re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

23
290
2

Year Published

2012
2012
2017
2017

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 321 publications
(315 citation statements)
references
References 24 publications
23
290
2
Order By: Relevance
“…The westernmost central Pacific SST anomaly broadly extends northeastwards into the Northern Hemisphere subtropics (to *30°N). This third SST pattern is also reminiscent of the so-called Pacific Meridional Mode, which may precede ENSO events (Vimont et al 2003;Chang et al 2007;Zhang et al 2009). The PC-3 monthly time series reveals no discernible linear trend in contrast to PC-1 and PC-2 (Fig.…”
Section: Leading Tropical Pacific Sst Patternsmentioning
confidence: 99%
“…The westernmost central Pacific SST anomaly broadly extends northeastwards into the Northern Hemisphere subtropics (to *30°N). This third SST pattern is also reminiscent of the so-called Pacific Meridional Mode, which may precede ENSO events (Vimont et al 2003;Chang et al 2007;Zhang et al 2009). The PC-3 monthly time series reveals no discernible linear trend in contrast to PC-1 and PC-2 (Fig.…”
Section: Leading Tropical Pacific Sst Patternsmentioning
confidence: 99%
“…The SST footprint then lasts into the following summer in the subtropics and potentially impacts equatorial zonal wind stress [Anderson, 2003;Vimont et al, 2001Vimont et al, , 2003. Under the SFM framework, two precursor patterns are prominent: The Pacific Meridional Mode based upon wind and SST anomalies in the eastern half of the North Pacific [Chang et al, 2007;Chiang and Vimont, 2004], and the Western North Pacific (WNP) pattern located in the western part of the basin [Wang et al, 2012[Wang et al, , 2013. Given the results from Figures 1d and 3, it is likely that the SST and wind anomalies of the WNP are able to produce a specific teleconnection that contributes to the dipole's formation.…”
Section: 1002/2014gl059748mentioning
confidence: 99%
“…Several other studies have then suggested that there is a positive feedback among subtropical low-level clouds, SST, and large-scale atmospheric circulation in the tropical Pacific (Philander et al 1996;Nigam 1997;Norris 2005;Clement et al 2009). The SST anomalies propagate from the subtropical NE and SE Pacific regions to the equatorial Pacific via the atmospheric wind-evaporation-SST (WES) feedback (Zhou and Carton 1998) and influence ENSO and the tropical Pacific climate (Chang et al 2007;Matei et al 2008;Okumura (2013); Zhang et al 2014). Cloud feedback in the subtropical stratocumulus regions could therefore lead to decadal anomalies in SST throughout the Pacific basin (cf.…”
Section: Introductionmentioning
confidence: 99%